Pengaruh Pemberian Asam Humat dan Kompos Tandan Kosong Kelapa Sawit terhadap Pertumbuhan dan Produksi Bawang Sabrang (Eleutherine americana Merr.) - Pingkan Welvari Sembiring; Haryati Haryati; Rosita Sipayung (Jurnal Agroekoteknologi, 2015)
The using of herbal medicine has increasing rapidly recently. One of the medical plant that has been developing is bawang sabrang. The aim of the research is to find out the proper dosage of humic acid and empty palm bunches compost for cultivated of bawang sabrang. Research was conducted at experimental field Faculty of Agriculture, University of Sumatera Utara, Medan about 25 m above sea level started from June until October 2014, used randomized block design, with two factors which are humic acid at several doses (0 g/plot, 1 g/plot, 2 g/plot, 3 g/plot) and palm empty fruit bunches compost at several doses (0 kg/plot, 0,5 kg/plot, 1 kg/plot dan 1,5 kg/plot) and was repeated three times. Data were analyzed by using ANOVA and continued with Duncan. Parameters were observed is net assimilation rate, relative growth rate, number of tillers, fresh bulb weight and number of bulb. The result showed that the effect of humic acid were increasing the net assimilation rate at fifth week after planting (WAP). The effect of empty palm bunches compost were increased the relative growth at four week and net assimilation rate at fifth week. The interaction between humic acid and empty palm bunches compost were increased the net assimilation rate at fifth week, but the effect of giving humic acid and empty palm bunches compost at number of tillers, fresh bulb weight and number of bulb parameters has not real.Keywords: humic acid, compost of empty palm bunches, Eleutherine americana Merr.